Ultrasound to guided epicutaneo-caval catheter insertion in newborn infants - Ren, Xiao-Ling; Wang, Man; Wei, Yu-Ru; Liu, Jing (Frontiers in Pediatrics, 2022)
Objective Recently, ultrasound has been increasingly used for epicutaneo-caval catheter (ECC) tip positioning; however, the selection of blood vessels for ECC still depends on the operator's subjective judgment. The objective of this study was to explore the value of ultrasound (US) in decision making regarding the great saphenous vein (GSV), tip navigation and tip location of ECC. Methods Catheterization through the GSV of the lower extremity was selected. The running condition of the GSV was assessed by using US, and the angle between the GSV and the femoral vein was observed and measured. We selected the GSV with a smaller angle to the femoral vein for ECC catheterization. Results ECC catheterization under ultrasound guidance increased the success rate at the time of catheterization from 82.5% to 100% (increase of 17.5%) and shortened the catheterization time from 56.1 ± 5.30 minutes to 31.5 ± 2.58 minutes on average (shortened by 44%). The incidence rate of catheter-related complications decreased by 58.2% catheter days from 6.80/1000 to 2.84/1000. Conclusion ECC insertion under the guidance of US has outstanding advantages, including significantly improving the success rate of one-time catheterization, shortening the time of catheterization, and reducing catheter-related complications.